2012
DOI: 10.5171/2012.703614
|View full text |Cite
|
Sign up to set email alerts
|

Do Customer Dissatisfaction and Variety Seeking Really Affect the Product Brand Switching? A Lesson from the Biggest Southeast Asia Mobile Telecommunication Market

Abstract: As the 21st century world would be a cellular age going by the phenomenal increase in cell phones worldwide, the Southeast Asia's market is experiencing a tremendous growth of mobile penetrations in the context of a region for developing countries with large population concentration. The mobile revolution has triumphed in Southeast Asia and become the key hub of the world's mobile & telecom market in terms of penetration and innovation, and promoted the best of mobile-based implementations in the region Asia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Empirically, this result is in line with the previous study was conducted by Junaidi and Dharmmesta (2002) who found that consumer dissatisfaction has a significance influence on brand-switching decision. Furthermore, this study result is also consistent with the previous study was conducted by Uturestantix et al, (2012) who conclude that consumer dissatisfaction has a positive significantly influence on brand switching.…”
Section: The Influence Of Dissatisfaction On Brand Switchingsupporting
confidence: 92%
See 4 more Smart Citations
“…Empirically, this result is in line with the previous study was conducted by Junaidi and Dharmmesta (2002) who found that consumer dissatisfaction has a significance influence on brand-switching decision. Furthermore, this study result is also consistent with the previous study was conducted by Uturestantix et al, (2012) who conclude that consumer dissatisfaction has a positive significantly influence on brand switching.…”
Section: The Influence Of Dissatisfaction On Brand Switchingsupporting
confidence: 92%
“…Previous study was conducted by Uturestantix et al, (2012) proves that sales promotion has a significantly positive effect on brand switching. Furthermore, study was conducted by Erman (2014) found evidenced that competitor advertisement has a positive significantly effect on brand switching.…”
Section: The Effect Of Promotion On Brand Switchingmentioning
confidence: 89%
See 3 more Smart Citations